Telaah Kritis Pemahaman Hijab dalam Framework Fatima Mernissi - Asyadily, Muhamad Hasan (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2019)
Hijab at this time, is a kind of clothing to cover the female genitalia from the sight of men who are not mahram in society in the form of headscarves or veils, so the hijab law is obligatory for Muslim women as a form of obedience to Allah and glory. However, according to Fatima Mernissi the hijab is not compulsory because it is a symbol of setback for women and the results of male manipulation, then he discusses the mistake of the hijab command with four points of view: language, history, interpretation and social. This research uses critical-analysis descriptive method is describing opinions about the hijab and doing critical-analysis to criticize ideas and thought. The results showed that the concept of the hijab offered by Mernissi is different from Islam: 1) defining hijab which means curtain or barrier used to criticize the concept of hijab as a cover for female genitalia, 2) hijab is only to distinguish between free women and slaves, and protect some of the women's categories, 3) understanding the obligation of the hijab is limited to Q.S. Al-Ahzab: 53 and 59.